Allowing for residual stresses in the cross-sections of compressed l-shaped columns during their design - Golodnov, A.I. (Автоматическая сварка, 2001)
A procedure has been developed for evaluation of the stress-strain state of I-shaped steel columns at all the stages of loading, including the hypercritical region. Design has been performed allowing for the fields of residual stresses, arising in the cross-sections of these columns. Разработана методика оценки напряженно-деформированного состояния стальных двутавровых стержней на всех стадиях нагружения, в том числе и в закритической области. Расчеты проведены с учетом полей остаточных напряжений, возникающих в сечениях этих стержней.